HUBUNGAN SELF-EFFICACY DAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMA PADA MATERI PERBANDINGAN TRIGONOMETRI - Sunarti Sunarti; Zubaidah R Zubaidah R; Romal Ijuddin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research is aimed to acknowledge the relationship between self-efficacy and high schoolers' mathematical communication ability in the material of Reciprocal Trigonometric. The research is one kind of correlation and ex post facto research, emerged with the qualitative approachment. Research subjects were all the students of X IPA 1 SMA Negeri 2 Sungai Raya. The technique used is measurement by giving self-efficacy scale and essay-form test of mathematical communication ability. The results showed that students' self-efficacy ability is in the medium category, while the mathematical communication ability stayed in high category. In order to gain the relationship between both variables, data analysis was conducted. Data was normally-distributed and had a linear correlation. After then, correlation analysis was done by performing Pearson Product Moment Test. The test gained Sig.(2-tailed) > α or 0.165 > 0.05. Thus, it can be concluded that there are no any relationship between self-efficacy and mathematical communication ability. In other words, no matter how high the rate of students' self-efficacy, it won't affect their mathematical communication ability. Keywords: Mathematical Communication Ability, Self-efficacy, Trigonometry Reciprocal